Simultaneous U and Th isotope measurements for U-series dating using MCICPMS - Kerber, Inga; Arps, Jennifer; Eichstädter, René; Kontor, Fabian; Dornick, Christoph; Schröder-Ritzrau, Andrea; Babu, Athulya; Warken, Sophie F.; Frank, Norbert (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2023)
U-series dating is a well-established tool for determining the ages of secondary carbonates in palaeoclimate science. We present a measurement method and data treatment protocol adapted for simultaneous Th and U isotope measurements with sub-‰ precision by using a combination of Faraday cups and a secondary electron multiplier on a multi-collector inductively coupled plasma mass spectrometer (MCICPMS). We systematically analyse the effect of undetected variations in raw data corrections on the accuracy of the activity ratios and ages using three representative speleothem and coral samples. On masses of 229 and 230 amu, we observe “ghost signals” for which we introduce appropriate correction factors. Not accounting for the “ghost signal” can lead to deviations from reference values of more than 10% for young materials. Other data corrections induce accuracy variability on ε-to ‰-levels. The resulting methodology permits measurements on the ε-level for (234U/238U) and on the (sub) permille-scale for (230Th/238U) determinations.